Development and validation of prediction models and rapid sensory methodologies to understand intrinsic bitterness of Cyclopia genistoides - Moelich, Erika Ilette (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD (Food Sc))--Stellenbosch, 2018.